Y90 Radiation Segmentectomy versus Microwave Ablation for Hepatocellular Carcinoma in Locations Suboptimal for Percutaneous Ablation - Kola, Olivia; Cieslak, John A.; Chauhan, Nirav; Gupta, Priya; Shukla, Pratik; Kumar, Abhishek (The Arab Journal of Interventional Radiology, 2024)
Purpose The purpose of our study was to evaluate outcomes following percutaneous microwave ablation (MWA) versus yttrium-90 (Y90) radiation segmentectomy (RS) for tumors in suboptimal locations for ablation.Materials and Methods Retrospective review (January 2014–July 2019) was performed on patients who underwent Y90-RS or MWA (with or without prior transarterial chemoembolization [TACE]) with curative intent for early-stage hepatocellular carcinoma (HCC) lesions in suboptimal locations for percutaneous ablation, defined as locations in which needle placement is within 5 mm of critical structures (liver dome, liver capsule, gallbladder, and hilum). The primary endpoints were treatment response as per the modified Response Evaluation Criteria in Solid Tumors criteria and complications.Statistical Analysis Fischer's exact test was performed for categorical variables, and Student's t-tests for nominal variables.Results Twenty-three lesions in 20 patients (13 male, 67 ± 8.8 years) and 30 lesions in 30 patients (18 male, 62.5 ± 10.6 years) were treated with Y90-RS and MWA (19 with prior TACE), respectively. There were no differences in demographics (p > 0.05). Mean tumor diameter was 2.9 ± 1.0 in those treated with Y90-RS and 2.3 ± 0.9 for MWA (p < 0.05). Lesions were located adjacent to the following structures: dome (n = 22), capsule (n = 16), hilum (n = 9), and gallbladder (n = 6). All patients were Eastern Cooperative Oncology Group performance status 0 to 1. Of the MWA cohort, 19 were Child-Pugh class A, 5 were B, and 6 were C and the mean pretreatment laboratory values were as follows: Model for End-stage Liver Disease sodium (MELD-Na) 12.7 ± 4.6, alpha-fetoprotein (AFP) 848 ± 3168.0, aspartate aminotransferase (AST) 71.9 ± 49.1, alanine aminotransferase (ALT) 48.0 ± 32.4, and total bilirubin 2.4 ± 2.7. Of the Y90-RS cohort, 15 were Child-Pugh class A, 4 were B, and 1 was C and pretreatment laboratory values were as follows: MELD-Na 10.5 ± 3.3 (Y90-RS), AFP 762.2 ± 1793.8 (Y90), AST 50.3 ± 30.5 (Y90), ALT 30.1 ± 16.9 (Y90), and total bilirubin 1.6 ± 1.1 (Y90). Complete response rate following Y90 was 96 versus 76% for MWA, with no disease progression after Y90-RS within the follow-up period. Three (13%) lesions demonstrated progression of disease (time to progression 6.3 months) after MWA. No grade > 2 toxicities or procedure-related complications were noted following Y90-RS. There were 7 major (arterioportal fistula with hemoperitoneum, pneumothorax, liver infarction, and capsular burn) and 3 minor complications following MWA.Conclusion Y90-RS is a valuable alternative to percutaneous MWA as a first-line therapy for early-stage HCC for tumors in suboptimal locations for ablation, offering a favorable treatment response and safety profile.
Keywords: ablation; hepatocellular carcinoma; locoregional therapy; microwave ablation; Y-90; yttrium